A Comment on Text, Time and Audience Understanding in Constitutional Law - Michael C. Dorf (Washington University Law Quarterly, 1995)
Professor Cunningham, in a provocative memorandum, asks how the legal landscape might change if courts interpreted statutes to reflect average citizens' understanding of statutory language.' This is an intriguing thought experiment and perhaps even a wise proposal. Rather than address Professor Cunningham's experiment directly, however, I would like to consider a variant of it that nicely highlights important issues in my own field, constitutional law. Substituting "the Constitution" for "statutes," we have the following question: What if the audience understanding of rules of, say, contract law, applied to the interpretation of the Constitution?
Keywords: Constitutional law